2020
DOI: 10.1007/s10681-020-02725-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a thrips resistance QTL in different Capsicum backgrounds

Abstract: Thrips are a worldwide threat to Capsicum because they damage fruits, flowers and leaves directly by feeding, and indirectly by vectoring tospoviruses such as tomato spotted wilt virus. Therefore, growers would benefit from thrips-resistant varieties. Previously, a quantitative trait locus (QTL) that provides resistance to Frankliniella occidentalis has been identified. Here we explore the potential of this QTL for breeding thrips-resistant varieties by studying its effect on two thrips species (i.e. F. occide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…DNA was extracted from the collected mapping population samples using DNeasy Plant Kits (Qiagen, Manchester, UK) according to the manufacturer protocol. Extracted samples were sent to Bejo Zaden BV (Warmenhuizen, The Netherlands) for genotyping according to the protocol of van Haperen et al ( 2020 ). Kompetitive allele specific PCR (KASP) primers for selected SNPs are provided in Additional File 10 .…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from the collected mapping population samples using DNeasy Plant Kits (Qiagen, Manchester, UK) according to the manufacturer protocol. Extracted samples were sent to Bejo Zaden BV (Warmenhuizen, The Netherlands) for genotyping according to the protocol of van Haperen et al ( 2020 ). Kompetitive allele specific PCR (KASP) primers for selected SNPs are provided in Additional File 10 .…”
Section: Methodsmentioning
confidence: 99%
“…In pepper, Maharijaya et al ( 2011 ) identified the wild Capsicum annuum accession CGN16975 as a potential source for thrips resistance. Further characterization of the resistance showed that the larval development is inhibited on young leaves (Maharijaya et al 2012 ; Van Haperen et al 2019 ), and that resistance was functional in several Capsicum backgrounds (Van Haperen et al 2020 ). QTL mapping for resistance to Frankliniella occidentalis was carried out in an F 2 population derived from an interspecific cross between the resistant Capsicum annuum CGN16975 and the susceptible Capsicum chinense CGN17219 (Maharijaya et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%